METODE PENYULUH AGAMA ISLAM DALAM MEMBINA PENGGUNA NARKOBA DI LEMBAGA PEMASYARAKATAN KELAS I MAKASSAR (Jurnal Washiyah: Jurnal Kajian Dakwah dah Komunikasi, 2024)
The main problem of this research is how the Method of Islamic Religious Counselors in Guiding Drug Users in Makassar Class I Penitentiary with two sub-problems, namely: 1) How are the efforts of Islamic religious counselors in guiding drug users in Makassar Class I Penitentiary? 2) What are the results of Islamic religious counselors in guiding drug users in Makassar Class I Penitentiary? This type of research is qualitative descriptive and located in Makassar Class I Penitentiary. The research approach used is the guidance and counseling approach. The primary data sources in this study are 3 Islamic Religious Counselors as key informants, KASI BIMKEMAS, and 4 drug teachers at Makassar Class I Penitentiary. Furthermore, the data collection methods used are observation, interviews, and documentation. After the data is collected, the researcher processes and analyzes the data through several stages, namely data reduction, data presentation, and drawing conclusions. The results of the study indicate that the method of Islamic religious instructors in guiding drug users in Makassar Class I Penitentiary is through personality training and guidance groups, which include religious lectures, consultation methods, and worship habits. The implication of this study is that Islamic religious instructors should provide more training so that employees do not repeat bad habits when they leave Makassar Class I Penitentiary. Inmates experienced a decrease in the desire to use drugs after undergoing the training program. Islamic religious instructors should have a method for providing counseling so that pardoners do not get bored with their counseling methods.